Seroepidemiología y factores de riesgo de Leptospira spp y lentivirus en hatos ovinos y caprinos del noreste de México. - Chávez Sánchez, Jesús Francisco (2019)
This study estimated leptospiral and small ruminant Lentivirus infections and seropositivity at herd- level, region and animal species. The risk factors associated to small ruminants in Nuevo León México were also estimated. 840 serum samples from 67 goat herds (n=441) and 52 sheep herds (n=399) from different economical regions obtained between July 2015 and August of 2016 were used. In addition, 90 serum samples were obtained from a high leptospiral seroprevalence herd from March 2018 to November 2018. For comparative purposes, 23 caprine serum samples from La Laguna, Coahuila region were analysed. The samples were considered positive when they demonstrated 50% of agglutination at a 1:100 dilution and on to one or more serovars. 25 urine samples obtained from a high leptospiral seroprevalence herd were cultured and analyzed by PCR (Lip L32 gene). MAT test was performed for detection of antileptospiral antibodies. The samples were considered positive when they demonstrated ≥50% of agglutination at a 1:100 dilution and on to one or more serovars. For small ruminant Lentivirus diagnosis, a cELISA test kit was used. The study revealed that 14.7% of goats and 12.5% of sheep were positives to one or more leptospiral serovars. In both species, dilutions varied between 1:100 to 1:400 reacting to the following serovars: Hardjo 7.8% (66/840), Icteroahemorrhagiae 1.9% (16/840), Bratislava 1.7% (14/840), and Pomona 1.2% (10/840). In small ruminant Lentivirus 24% of goats and 14.28% of sheep were positives, from which Galeana district showed the highest prevalence with 43.3% followed by Apodaca district with 38.8%. Risk factors were established by chi square test obtaining a strong association between prevalence and variables determined by a survey. In Leptospira the risk factors